P270 TELL ME HOW LONG WILL YOU STAY … TELL ME HOW LONG HOW LONG … ANALYSIS OF THE DURATION OF HOSPITAL STAY (HOSPITAL LENGTH OF STAY) OF ELDERLY PATIENTS WITH EMBOLISM: EXPERIENCE OF 4 YEARS IN FIRST AID. (18th May 2022) - Savioli, G; Ceresa, I; Amedeo, M; Martignoni, A; Lava, M; Muzzi, A; Fumoso, F; Lapia, F; Brattoli, M; Bressan, M
Abstract: Premise: Pulmonary embolism is a disease still characterized by high mortality. It requires emergency department resources to be diagnosed promptly and can require lengthy hospital care. Purpose: to assess which parameters, in the real life of an Emergency Department, correlate with the duration of a hospitalization for pulmonary embolism (hospital LOS). Methods: Single–center retrospective observational study, on all geriatric patients (> 75) who entered our ED, where they were diagnosed with acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and Years), and for the presentation of the risk of mortality at 30 days (sPESI). We analyzed all the blood chemistry and blood gas analyzes performed upon access to the emergency room. We then had all chest CTs retested by an experienced radiologist. We also analyzed vital parameters and the various shock indexes from these derivatives. We then analyzed whether patients had massive pulmonary embolism or the presence of organ damage (right ventricular dilation, pulmonary artery dilation and presence of pulmonary infarction). Results: We enrolled 247 patients, all in need of hospitalization for acute pulmonary embolism. The average age is 83 with female precalence (F = 63%). Regarding the length of hospital stay, the presence of massive embolism shows a good statistical correlation (p < 0.01), while the presence of organ damage seems irrelevant (p > 0.05). The need for resuscitation care and the high sPESI index also show no correlation (p > 0.05). Age and vital signs (blood pressure, respiratory rate, heart rate) as well as derived shock indices are unrelated (rho∼0; p > 0.05). A weak correlation is instead present with high D–Dimer values (rho∼0.20; p < 0.005) while the other blood samples do not show correlation (rho∼0; p > 0.05). No correlation for the blood gas analysis parameters taken into consideration (pH; pO2; pCO2; lactates). Conclusions: The study suggests that the presence of massive pulmonary embolism and to a lesser extent high D–Dimer values correlates with a long hospital stay.